Pyrethrin accumulation in elicited hairy root cultures of chrysanthemum cinerariaefolium - Khan, Shamshad A.; Verma, Priyanka; Banerjee, Suchitra; Chaterjee, Arnab; Tandon, Sudeep; Kalra, Alok; Khaliq, Abdul; Rahman, Laiq Ur (Plant Growth Regulation, 2017)
The flowers of Pyrethrum (Chrysanthemum cinerariaefolium) are known to contain Pyrethrins that are naturally occurring potential insecticide. Hairy roots were induced from leaves of C. cinerariaefolium using Agrobacterium rhizogenes strain A4. The root clones were characterized in to four groups i.e. thick, unbranched (D2 and D5), thin, highly branched (D3), thick, branched (B2) and thick, highly branched (D1, D6). Six established hairy root clones showed the presence of pyrethrin and were selected for elicitation studies. Growth kinetics studies revealed highest growth index in hairy root clone D1 (592.0) followed by D6 and D3 on dry weight basis after 40 days of culture. The maximum pyrethrin content was found in the clone D3 (7.2 mg/g dw) which is comparable to the flowers obtained from the variety "Avadh". Hairy root clone D2 (5.2 mg/g dw) and D6 (1.3 mg/g dw) contained pyrethrin but in less amount as compared to clone D3. The PCR analysis showed the presence of rol B and rol C genes in all the six hairy root clones while rol A was detected only in D2 clone. The methanolic extract of D3 clone showed antifungal activities against phytopathogenic fungal strains which were found maximum against Curvuleria andropogonis followed by Colletotrichum acutatum and Rhizoctonia solani. Hairy root clones D2, D3 and D6 were elicited with culture filtrate of endophytic fungus (Fusarium oxysporum) and bacteria (Bacillus subtilis). The culture filtrate (4.0 %v/v) of both the fungal and bacterial origin was found to be effective in enhancing the pyrethrin content in all the tested hairy root clones. Clone D3 showed maximum pyrethrin content on elicitation with F. oxysporum (9.7 mg/g dw) and B. subtilis (9.7 mg/g dw) culture filtrate, which is 32 % higher than the non elicited D3 hairy roots (7.2 mg/g dw). F. oxysporum also enhanced the hairy root growth resulting into the higher biomass yield of D3 (50 %) and D2 (76 %) in comparison to control non elicited hairy root clones of D3 and D2, respectively leading to higher pyrethrin yield.

Sustainable bioprocess technology for producing food-flavour (+)-γ-decalactone from castor oil-derived ricinoleic acid using enzymatic activity of Candida parapsilosis: Scale-up optimization and purification using novel composite - Syed, Naziya; Singh, Suman; Chaturvedi, Shivani; Kumar, Prashant; Kumar, Deepak; Jain, Abhinav; Sharma, Praveen Kumar; Nannaware, Ashween Deepak; Chanotiya, Chandan Singh; Bhambure, Rahul; Kumar, Pankaj; Kalra, Alok; et al. (Journal of Biotechnology, 2024)
Ricinoleic acid (RA) from castor oil was employed in biotransformation of peach-flavoured gamma-decalactone (GDL), using a Candida parapsilosis strain (MTCC13027) which was isolated from waste of pineapple crown base. Using four variables-pH, cell density, amount of RA, and temperature-the biotransformation parameters were optimized using RSM and BBD. Under optimized conditions (pH 6, 10 % of microbial cells, 10 g/L RA at 28 degrees C), the conversion was maximum and resulted to 80 % (+)-GDL (4.4 g/L/120 h) yield in shake flask (500 mL). Furthermore, optimization was achieved by adjusting the aeration and agitation parameters in a 3 L bioreactor, which were then replicated in a 10 L bioreactor to accurately determine the amount of (+)-GDL. In bioreactor condition, 4.7 g/L (>85 %) of (+)-GDL is produced with 20 % and 40 % dissolved oxygen (1.0 vvm) at 150 rpm in 72 h and 66 h, respectively. Further, a new Al-Mg-Ca-Si composite column-chromatography method is developed to purify enantiospecific (+)-GDL (99.9 %). This (+)-GDL is 100 % nature-identical as validated through 14C-radio-carbon dating. Thorough chemical investigation of enantiospecific (+)-GDL is authenticated for its use as flavour. This bioflavour has been developed through a cost-effective biotechnological process in response to the demand from the food industry on commercial scale.
Keywords: (+)-gamma-Decalactone; Al-Mg-Ca-Si composite; Bioflavour; Candida parapsilosis; castor oil; Food-waste